Integrasi Pendidikan Karakter Berbasis Qurani dan Kearifan Lokal Bugis - Yusuf, Yusuf (Jurnal Studi Agama dan Masyarakat, 2015)
This article studies about education character bases on the quranic values and local wisdom, particularly Bugis culture. Conceptually,